Advanced localization techniques for autonomous road vehicles: Integrating ultrasonic and beacon-based systems - D. N. Nithilam; B. Paulchamy (International Journal of Advanced Robotic Systems)
In the realm of autonomous highway navigation, a critical initial task is accurately localizing the vehicle on the road. This necessitates the integration of data from various sensors alongside information gleaned from road maps to ensure precision and reliability. This research addresses the critical need for precise localization of autonomous road vehicles, essential for safe and efficient navigation in complex urban environments. Traditional GPS-based systems often face limitations in accuracy, especially in urban canyons and environments with tall buildings. Thus, alternative localization methodologies are essential to ensure reliable autonomous driving. Two novel localization methodologies are explored: an Ultrasonic Indoor Positioning System with a Single Beacon Range-Based Localization Approach. The Ultrasonic Indoor Positioning System involves deploying ultrasonic transmitters on vehicles and receivers at known locations, utilizing time-of-flight calculations for distance estimation. Calibration techniques and outlier rejection enhance system accuracy. Conversely, the single beacon method integrates beacon range measurements with vehicle speed and heading information using an Extended Kalman Filter algorithm for iterative position estimation. Experimental evaluations demonstrate the effectiveness of both methodologies. The Ultrasonic Indoor Positioning System achieves position accuracies of 3–4 cm for static targets and 4–7 cm for moving targets, with a minimal error rate. In comparison, the single beacon approach achieves localization within approximately 30 cm of the true position, with a range measurement accuracy of 1–4 cm and a settling time of around 50 s. These results highlight the feasibility and reliability of employing these methodologies for autonomous road vehicle localization. The research underscores the significance of alternative localization techniques in enhancing the autonomy and safety of road vehicles. By leveraging ultrasonic and beacon-based systems, the proposed methodologies offer robust solutions for precise localization, even in challenging urban environments. These findings contribute to the advancement of autonomous driving technologies, paving the way for safer and more efficient transportation systems of the future.